Social Entrepreneurship-Based Assisted Village With The Concept of Production House As An Effort to Improve The Economy Coastal of Punaga Village, Takalar District - Syahban Nur; Wahyuddin; Dian Pramana Putra (Indonesian Journal of Community Services, 2023)
Punaga village is one of the villages affected by the pandemic which resulted in unstable economic conditions, Punaga village is inhabited by 2772 people and the majority of the people work as seaweed farmers, each family head can produce an average of three tons in one season. This makes Punaga village a village that has the potential to be developed in terms of seaweed processing. Empowerment of women, especially housewives who do not go directly to the sea with their husbands, can be empowered with entrepreneurship-based training activities with the concept of a production house with a variety of processed foods and skills made from seaweed. The online-based Production House facility can be utilized as a place for continuous training and also as an exhibition place for the work of housewives, and can be accessed by the visiting community or Edu-tourism and can be accessed via the web or social because it is online-based. Thus, it will also indirectly help the promotion process to attract the interest of the general public to buy and ultimately have an impact on increasing the income of the Punaga Village community.